2020
DOI: 10.1038/s41419-020-03114-4
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mTORC1 by LSECtin in macrophages directs intestinal repair in inflammatory bowel disease

Abstract: Damage to intestinal epithelial cells and the induction of cellular apoptosis are characteristics of inflammatory bowel disease. The C-type lectin receptor family member LSECtin promotes apoptotic cell clearance by macrophages and induces the production of anti-inflammatory/tissue growth factors, which direct intestinal repair in experimental colitis. However, the mechanisms by which the phagocytosis of apoptotic cells triggers the pro-repair function of macrophages remain largely undefined. Here, using immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…mTOR regulates the differentiation of T cells, as it accelerates the polarization of Th17 and Th1 cells and depresses regulatory T cell differentiation ( Delgoffe et al, 2009 ). Additionally, the increased activation of mTOR leads to an elevation in inflammatory cytokines levels through differentiating type I macrophages ( Li et al, 2020 ). Furthermore, the NLR family pyrin domain containing 3 (NLRP3) inflammasome is one of the main inflammatory pathways that is triggered by mTOR activation ( Saber et al, 2020a ; Saber and El-Kader, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…mTOR regulates the differentiation of T cells, as it accelerates the polarization of Th17 and Th1 cells and depresses regulatory T cell differentiation ( Delgoffe et al, 2009 ). Additionally, the increased activation of mTOR leads to an elevation in inflammatory cytokines levels through differentiating type I macrophages ( Li et al, 2020 ). Furthermore, the NLR family pyrin domain containing 3 (NLRP3) inflammasome is one of the main inflammatory pathways that is triggered by mTOR activation ( Saber et al, 2020a ; Saber and El-Kader, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with these findings, Li et al reported that liver and lymph node sinusoidal endothelial cell c‐type lectin (LSECtin) in macrophages facilitates the phagocytosis of apoptotic cells in the gut mucosa, that in turn, promotes the proliferation of intestinal cells and the healing process in colitis. They found that mTOR is the major regulator of LSECtin whose activation markedly increases LSECTin levels in the macrophages obtained from UC tissues and in the macrophages of DSS‐induced colitis [43]. In contrast, Zhao and colleagues demonstrated that AKT/mTOR activation in Treg cells of the gut mucosa improved their activity in vitro and exacerbated colitis in DSS mice [44].…”
Section: Pi3k Signaling and Ucmentioning
confidence: 99%
“…In the homeostatic intestine, IMφs actively phagocytize the effete IECs within the intestinal villi to maintain epithelial turnover 72 . When the IEC barrier is mechanically injured, IMφs accumulate around the wound bed and ensure effective epithelial healing 73,74 . In the literature, blood‐derived macrophages from healthy donors, or patients with IBD, displayed a CD206 + CCL18 + CD14 low/− phenotype upon IL‐4 treatment, thus acquiring the ability to accelerate epithelial wound healing by producing TGF‐β 75 .…”
Section: Crosstalk Between Iecs and Imφsmentioning
confidence: 99%
“…72 When the IEC barrier is mechanically injured, IMφs accumulate around the wound bed and ensure effective epithelial healing. 73,74 In the literature, blood-derived macrophages from healthy donors, or patients with IBD, displayed a CD206 + CCL18 + CD14 low/− phenotype upon IL-4 treatment, thus acquiring the ability to accelerate epithelial wound healing by producing TGF-β. 75 IL-4-primed macrophages were also found to secrete miR-590-3p-containing exosomes, which then facilitated epithelial repair by activating the LATS1/YAP/β-catenin pathway.…”
Section: Imφs Communicating With Iecs-feedback Mechanismsmentioning
confidence: 99%